Kinematic twist-three contributions to pseudo- and quasi-GPDs and translation invariance - V. M. Braun (Journal of High Energy Physics, 2023)
Abstract We present explicit expressions for the tree-level “kinematic” twist-three contributions to the nucleon matrix elements of gauge-invariant nonlocal quark-antiquark operators which can be used in lattice calculations of generalized parton distributions (GPDs). These contributions in particular restore the translation invariance of the results up to higher twist four. The calculated twist-three corrections are logarithmically enhanced as compared to the leading twist, and are discontinuous at the kinematic points x = ±ξ.